Les paradigmes de la gestion transfrontalière à l'épreuve du Dniepr - Gabrielle Bouleau; Pierre Lorillou (VertigO, 2003)
International guidelines for transboundary waters have been developed for riparian countries facing economical competition, having very different legislations, culture and languages. Such guidelines recommend to set an international monitoring system because most of the time it is missing. Riparian countries of the Dniper have a common recent past which make things quite different from most international basins. Therefore such guidelines must be adapted to acknowledge institutional opportunities of the New Independant States. Moreover, the industrial heritage and the economical transition are big constraints to take into account. Retraining could be a key factor for the future of the Dniper basin.